THE PERCENTAGE OF T-LYMPHOCYTE AND NKT CELLS IN PERIPHERAL BLOOD OF PATIENTS WITH ACTIVE AND INACTIVE PULMONARY TUBERCULOSIS - Akbulut, H. Handan; Celik, Ilhami; Deveci, Figen; Akbulut, Ayhan (Nobel Ilac, 2011)
Objective: T-lymphocyte and natural killer T (NKT) cells have an important role in viral and other intracellular infections. In the present study, it was aimed to investigate whether a difference of T and NKT cells ratio between active and inactive pulmonary tuberculosis (PT) patients. Material and Method: Seventy five active and 25 inactive Pulmonary tuberculosis (PT) patients and 20 healthy individuals, having no disease were included in the study Two mL venous blood samples were withdrawn from all patients and healthy subjects for studying T and NKT cells. Total T cells and NKT cells [CD3+, and CD3+CD(16+56)+] were established from EDTA blood. The blood cells were analyzed by Coulter EPICS XL-MCL (Beckman Coulter, USA) flow cytometry equipment. Results: Percentages of total T cells were not found to be different between active and inactive PT cases, but they were significantly lower than in controls (64.9 +/- 9.6, 65.2 +/- 5.4, 73.2 +/- 7.1, respectively, p=0.001 for active and p=0.003 for inactive patients compared with controls). NKT cells percentages were not statistically different between in patients with active and inactive. In addition, NKT percentages in active and inactive PT patients did not differ statistically than healthy subjects (5.25 +/- 3.93, 5.11 +/- 2.48, 5.91 +/- 6.09 respectively). Conclusion: Many studies showed NKT cells can play an important role for protection from M. tuberculosis infections but in the present study, we could not found any difference regarding NKT cells among active, inactive PT patients and healthy controls. But percentages of total T cells were found significantly lower in patients with tuberculosis compared with controls. The fewness of T-lymphocyte percentage in peripheral circulating blood in patients with tuberculosis compared to the healthy peoples that shows the importance of the T-lymphocyte in the pathogenesis of tuberculosis.
Keywords: T-lymphocyte; NKT cell; tuberculosis